The Effect of Audit Committee Effectiveness and Operating Cash Flow on Earnings Persistence in Banking Companies Listed on the Indonesia Stock Exchange - Deviyana, Alvira Putri; Azis, Azolla Degita; Bimo, Widhi Ariyo (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
This study aims to determine the effect of the effectiveness of the audit committee and operating cash flow on earnings persistence in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The research method used in this research is a quantitative approach with descriptive methods where the results of data research are in the form of exposure to statistical results processed using E-views version 12 software. The study used secondary data in the form of annual financial reports of banking companies for the 2018-2021 period. Sampling used purposive sampling technique and there were 29 banking companies with a period of four years. Based on the analysis that has been carried out in this study, the results show that the variable effect of the effectiveness of the audit committee and operating cash flow has no effect on earnings persistence. And simultaneously the variable effectiveness of the audit committee and operating cash flow has no effect on earnings persistence.